Veterinarians' perception of veterinary telemedicine in Guayaquil - Cevallos Acuña, Nayely Melissa; Márquez Zamora, Liz Andrea; Salazar Mazamba, María de Lourdes; Márquez Cabrera, Israel Emilio (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
Telemedicine is defined as the use of digital platforms to facilitate remote interaction between the client and the veterinarian to follow up on the animals without requiring a face-to-face consultation. The objective of this study was to analyze the perception of veterinarians about telemedicine in Guayaquil. A structured survey was applied to 146 practicing professionals. The approach was quantitative, descriptive and cross-sectional. The instrument was validated using Cronbach's alpha coefficient, obtaining 0.76. Data analysis was performed with descriptive statistics in SPSS v.26. A 95 % confidence interval was obtained (3.23, 3.51), indicating a tendency between neutral and in agreement. A low adoption of this technological tool was evidenced, despite its potential and benefits. It is recommended to promote continuous training and establish clear rules for its use.
Keywords: Adoption; perception; digital platforms; veterinarians; telemedicine